2013
DOI: 10.1007/s11027-013-9450-6
|View full text |Cite
|
Sign up to set email alerts
|

A Geographic Information System (GIS)-based approach to adaptation to regional climate change: a case study of Okutama-machi, Tokyo, Japan

Abstract: Recently, local governments have an increasing need to take extensive and effective local measures to adapt to regional climate change, but have difficulty knowing how and when to adapt to such change. This study aims: 1) to characterize an efficient and cost-effective database management tool (DMT) for developing a Geographic Information System (GIS) based approach to using observed and projected data, for decision-making by non-expert government authorities, and 2) to document how DMT can be used to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Spatial reasoning is crucial for analysing and synthesising findings from sources including in-situ sensors and satellite imagery. Researchers draw on geographic information to reveal how the planet has changed through the years, predict the transformations that are yet to come, and communicate what they learn to policymakers and the public (e.g., [ 38 41 ]).…”
Section: The Role Of Geospatial Data Methods and Tools In The Measure...mentioning
confidence: 99%
“…Spatial reasoning is crucial for analysing and synthesising findings from sources including in-situ sensors and satellite imagery. Researchers draw on geographic information to reveal how the planet has changed through the years, predict the transformations that are yet to come, and communicate what they learn to policymakers and the public (e.g., [ 38 41 ]).…”
Section: The Role Of Geospatial Data Methods and Tools In The Measure...mentioning
confidence: 99%
“…The biggest limitation of the general model is the difficulty in collecting data relating market prices; therefore, it may influence the accuracy of models. Besides, a number of studies applied Geographic Information System (GIS) or satellite estimates to locate damage areas to assess the impact of natural hazards [30][31][32][33][34]. GIS may become a good solution in incorporating the complexities of the spatial dimension within the analyses of climate change and adaptation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There exist various assessment studies that have attempted to characterize vulnerability combining both social and ecological indicators and RS data at different spatiotemporal scales in related literature (Füssel and Klein 2006;Ostrom 2009;Brondizio et al 2016;Sebesvari et al 2016). For example, Bai et al (2014) combined GIS, climate change projections, and observed socioeconomic data on a regional scale in order to characterize vulnerability as a function of its underlying components of exposure, sensitivity, and adaptive capacity in order to assist in decision-making and stakeholders. Murthy et al (2015) computed agricultural drought vulnerability index in India using 11 ecological indicators of the same vulnerability components and moderate-resolution imaging spectroradiometer (MODIS) data between 2001 and 2012.…”
Section: Introductionmentioning
confidence: 99%